The Influence of Local Government Spending Effiency on Human Development in Indonesia - Putri Maziya Ikhsanti; Candra Fajri Ananda (Journal La Sociale, 2026)
This study aims to measure the efficiency of local government spending in improving human development across 34 provinces in Indonesia during 2015–2024, and to identify the factors influencing efficiency. A two-stage approach is employed, consisting of Data Envelopment Analysis (DEA) and Tobit regression. The results show that the average efficiency of provincial spending fluctuates and has not yet reached full efficiency. Several provinces such as the Riau Islands, the Special Region of Yogyakarta, the Bangka Belitung Islands, Maluku, and North Kalimantan reached relative efficiency (score = 1) in multiple years, whereas Central Java and East Java tended to record low efficiency scores. The Tobit estimates indicate that GRDP per capita and population density have a positive and significant effect on efficiency, while the poverty rate has a negative and significant effect. These findings confirm that improving human development depends not only on the size of public spending, but also on provinces ability to convert public expenditures into human development outcomes, which is shaped by fiscal capacity, social conditions, and the spatial structure of regions.